The Impact of Medical Simulations on Reducing Medical Errors - Leszczyńska-Knaga, Elżbieta; Jakubczyk, Natalia; Kurowski, Marek; Kaczupska, Karolina; Gliwa, Anna; Ryglewicz, Monika; Fabian, Dariusz; Rutkowska-Kawalec, Weronika; Moczydłowski, Paweł; Michalczuk, Karolina (Journal of Education, Health and Sport, 2025)
Modern medical simulations are an effective tool for reducing medical errors by providing healthcare professionals with the opportunity to practice in a safe, controlled environment. These simulations help refine both technical and non-technical skills, including communication and teamwork, essential for ensuring patient safety. By engaging in repeated practice, learners can build confidence and competence in performing procedures, thus minimizing the risk of errors when interacting with real patients. Medical errors remain a significant global concern, contributing to high morbidity and mortality rates. As healthcare errors are ranked as the third leading cause of death in developed countries, simulation technology offers a valuable solution to improve clinical skills and decision-making. High-fidelity mannequins, virtual reality, and other simulation tools allow healthcare workers to master routine and complex medical procedures, from airway management to advanced surgical interventions. In addition to technical training, simulations enhance interpersonal skills, promoting effective communication and collaboration within medical teams. Poor communication is often a primary cause of medical errors, but simulation-based training enables learners to practice and improve these skills in realistic scenarios. Furthermore, feedback and debriefing after simulations consolidate learning, foster reflective practice, and support ongoing professional development. This review explores the role of medical simulations in reducing medical errors, highlighting both the technical and non-technical aspects of these training methods and their impact on patient safety and healthcare outcomes.